In Situ Surface Modification of Ni-YSZ with BaZrO3 for Enhancing the Sulfur Tolerance of Ni-YSZ Anode. Issue 9 (1st January 2016) - Kwon, Ohhun; Sengodan, Sivaprakash; Lim, Chaehyun; Jeong, Hu Young; Shin, Jeeyoung; Ju, Young-Wan; Kim, Guntae
Abstract : In this work, we report on a BaZrO3 (BZO) modified NiO-YSZ anode fabricated by co-sintering of NiO-YSZ and BaCO3 for SOFCs. The BZO modified Ni-YSZ anode shows stable electrochemical performance in H2 fuel containing a high level of 100 ppm sulfur for more than 100 hours. On the other hand, an unmodified Ni-YSZ anode degrades significantly in 100 ppm sulfur containing H2 fuel. The obtained results demonstrate that the BZO in the Ni-YSZ is an excellent catalyst for enhancing the sulfur tolerance of the conventional Ni-YSZ anode. Moreover, the surface modification strategy is simple and cost-effective, and thereby can promote commercialization of Ni-YSZ anode supported cells.